Effectiveness of Different Models of Physical Activity in Improving the Physiological Characteristics of Girls Studying at University - Banakh, Volodymyr; Iedynak, Gennadii; Blavt, Oksana (Journal of learning theory and methodology (Online), 2025)
Objectives.  The purpose of the study was to determine the best of two models of physical activity in improving the physiological characteristics of girls during the first year of university study.  Material and methods. The study involved 79 girls, each aged 17.7±0.4 years, belonging to the most numerous thoracic and muscular somatotypes, with no restrictions on the use of different amounts of physical activity, and were randomly assigned to experimental and control groups. A modified Stefko-Ostrovsky method was used to diagnose the somatotype. We studied blood pressure, heart rate in different situations, lung capacity, vital capacity, vital index, strength index, and Robinson index. At the beginning and end of the experiment, which lasted for one academic year, the necessary empirical data were obtained using well-known functional tests. Regarding girls’ physical activity, the experimental groups used the model developed by us, and the control groups used the traditional model of physical activity during the first year of study at a higher education institution.  Results. At the beginning of the study, the values of functional characteristics in experimental and control groups practically did not differ from each other, and the nature of the distribution of individual values in each group corresponded to normal. The use of the developed model by girls with thoracic and muscular somatotypes led to the improvement of 7 and 8 of all 9 characteristics studied, respectively, while the use of the traditional model led to their manifestation at the level achieved earlier. At the end of the study, in both experimental groups, the results of detection of all characteristics were significantly better (at the level of p < 0.05÷0.000) than in the control groups, except for SBP of girls with thoracic, SBP and RI of girls with muscular types.  Conclusions. The author’s model of physical activity was experimentally proved to be much more effective than the traditional one in improving the physiological characteristics of girls during the first year of study at university. The following features were revealed peculiarities in the change of parameters of physiological characteristics of girls with different somatotypes will contribute to the increase of efficiency of personalization of organizational, content and differentiation of normative bases of university physical education.